Book Review: Mark EDWARDS, Dimitrios PALLIS and Georgios STEIRIS (eds.), The Oxford Handbook of Dionysius the Areopagite, Oxford University Press, Oxford 2022 - ΒΙΓΚΛΑΣ Κατελής (Byzantina Symmeikta, 2023)
Book Review: Mark EDWARDS, Dimitrios PALLIS and Georgios STEIRIS (eds.), The Oxford Handbook of Dionysius the Areopagite, Oxford University Press, Oxford 2022